2007
DOI: 10.1177/1461444807081228
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the fragmentation of the cyberpublic: from consensus to contestation

Abstract: Recently there has been some debate between deliberative democrats about whether the internet is leading to the fragmentation of communication into `like-minded' groups.This article is concerned with what is held in common by both sides of the debate: a public sphere model that aims for all-inclusive, consensus seeking rational deliberation that eliminates inter-group `polarizing' politics. It argues that this understanding of deliberative democracy fails to adequately consider the asymmetries of power through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
0
23

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(187 citation statements)
references
References 38 publications
(48 reference statements)
3
161
0
23
Order By: Relevance
“…Sin embargo, el desarrollo de las posibilidades democráticas en esta nueva esfera digital también se encuentra con limitaciones significativas como la brecha digital (Dahlberg, 2007), la polarización de los discursos (Benkler, 2015) en un espacio que tiende a dispersar las opiniones (Rendueles y Sádaba, 2014), que favorece la vigilancia, el control y la censura (Mozorov, 2011), donde la actividad política está concentrada en los partidos tradicionales (Papacharissi, 2009) cuya comunicación está orientada a los medios de comunicación generalistas (Dader et all, 2011) y la participación ciudadana está basada en actos pasivos, inofensivos, personales y de entretenimiento (Rotman, Preece y Vieweg, 2011;Mozorov, 2011).…”
Section: Abstract: During a Period Of Crisis Of Traditional Institutiunclassified
See 1 more Smart Citation
“…Sin embargo, el desarrollo de las posibilidades democráticas en esta nueva esfera digital también se encuentra con limitaciones significativas como la brecha digital (Dahlberg, 2007), la polarización de los discursos (Benkler, 2015) en un espacio que tiende a dispersar las opiniones (Rendueles y Sádaba, 2014), que favorece la vigilancia, el control y la censura (Mozorov, 2011), donde la actividad política está concentrada en los partidos tradicionales (Papacharissi, 2009) cuya comunicación está orientada a los medios de comunicación generalistas (Dader et all, 2011) y la participación ciudadana está basada en actos pasivos, inofensivos, personales y de entretenimiento (Rotman, Preece y Vieweg, 2011;Mozorov, 2011).…”
Section: Abstract: During a Period Of Crisis Of Traditional Institutiunclassified
“…Estos movimientos responden a un rasgo principal que los diferencia de los movimientos precedentes: se expresan con la toma del espacio público por parte de multitudes auto-convocadas y auto-organizadas, fundamentalmente a través de las TIC (Haro y Sampedro, 2011). Desde la red, como soporte y como base (Sánchez-Duarte y Magallón-Rosa, 2015), los NMS han encontrado formas sencillas de volver a conectar con los ciudadanos, y especialmente con los jóvenes, frente a la desafección de las instituciones y de las políticas formales (Castells, 2009; Van Laer y Van Aelst, 2010;Della Porta, 2011).Sin embargo, el desarrollo de las posibilidades democráticas en esta nueva esfera digital también se encuentra con limitaciones significativas como la brecha digital (Dahlberg, 2007), la polarización de los discursos (Benkler, 2015) en un espacio que tiende a dispersar las opiniones (Rendueles y Sádaba, 2014), que favorece la vigilancia, el control y la censura (Mozorov, 2011), donde la actividad política está concentrada en los partidos tradicionales (Papacharissi, 2009) cuya comunicación está orientada a los medios de comunicación generalistas (Dader et all, 2011) y la participación ciudadana está basada en actos pasivos, inofensivos, personales y de entretenimiento (Rotman, Preece y Vieweg, 2011;Mozorov, 2011).En este trabajo nos centramos en el máximo exponente de este ciclo de acción social en España, el Movimiento 15M [15M], también conocido internacionalmente como indignados, y su movimiento precedente, el Movimiento por la Vivienda Digna [MVD]. El análisis estructural de sus sitios web (Schneider y Foot, 2004) en las campañas electorales de 2008 y 2011 nos ha permitido 1) describir cómo los NMS usan las web y su evolución; 2) revelar la estructura de las propias organizaciones; y 3) comprobar que el MVD es un antecedente clave, laboratorio de ideas y de prácticas del Movimiento 15M.…”
unclassified
“…Both demographic and socio-economic variables are at the heart of volatility (Chiaramonte and Emanuele 2015) and party fragmentation (Anckar 2000;Gabriel, Hoffmann-Martinot, and Savitch 2000;Dahlberg 2007;Bischoff 2013) at the municipal level. In municipal elections, population size is a key determinant of the political trust of residents (Denters 2002(Denters , 1843 and on voter turnout.…”
Section: Effects Of Municipal Conditions On Volatility and Fragmentationmentioning
confidence: 99%
“…Increased levels of volatility and fragmentation have been identified as two major characteristics of western democracies in recent decades (WeBels et al 2014). Several studies found electoral volatility (Chiaramonte and Emanuele 2015) and party fragmentation (Anckar 2000;Gabriel, Hoffmann-Martinot, and Savitch 2000;Dahlberg 2007;Bischoff 2013) to be associated with demographic and socio-economic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Small working groups generated ideas for presentation to the general assembly and actions to be taken were then determined by consensus, determined using hand signals, in a method that resembles the debate, deliberation and consensus formation (or contestation) process in online spaces such as message boards, Facebook groups, Twitter, wikis, and blogs (see, for example, Dahlberg, 2001Dahlberg, , 2007Dahlberg, , 2011Dahlgren, 2001;Fenton & Downey, 2003). OWS even avoided designating official spokespeople to represent the group (Bennett & Segerberg, 2016, p. 92).…”
Section: Ows Processes-an Overviewmentioning
confidence: 99%